The Effect Of Environmental Awareness, Carbon Performance, Carbon Volume, And Carbon Emission Disclosure On Firm Performance - Angelina Yuvita Todryyanti Mai; Etty Murwaningsari (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2024)
Purpose – This study seeks to investigate, through empirical analysis, how environmental awareness, carbon performance, carbon intensity, and disclosure of carbon emissions influence a firm's performance.  Design/methodology/approach – The study employs quantitative methods, employing purposive sampling techniques to select 182 companies within the sector of Consumer Non-Cyclicals listed on the Indonesia Stock Exchange between 2021 and 2022.as samples. Secondary data is obtained from annual reports and sustainability reports  available on www.idx.com and respective company websites, are utilized for analysis. Analysis of panel data regression is carried out utilizing Eviews 12 Software. Findings – The results of this study suggest that the disclosure of carbon emissions has a positive effect on firm performance. Conversely, findings indicate that variables such as environmental awareness, carbon performance, and carbon volume do not significantly affect firm performance.  Research limitations/implications – Based on the conclusions presented, researchers can offer recommendations to enhance the quality of future research. Suggestions include incorporating additional variables that may influence firm performance and advising companies to consider factors impacting their performance.